Remarkable Solvent Effects of Structurally Diverse Alcohols on Nucleophilic Displacement Reactions with Halide Ions. (29th June 2018) - Moon, Byung Seok; Lee, Byoung Se; Chu, So Young; Kim, Dong Wook; Chi, Dae Yoon
Abstract : Solvent effects on nucleophilic displacement reactions of alkyl mesylates with halide ions were investigated in a series of protic alcohol solvents. In consideration of Hughes and Ingold's principle, the reaction rates were found to correlate well with the normalized solvent polarities ( E T N ) in all halide reactions.